Repatriacja amerykańskich jeńców wojennych i cywilów z radzieckich jednostek repatriacyjnych na terenie Polski w latach 1944-1945 (2023)
THE REPATRIATION OF AMERICAN PRISONERS OF WAR AND CIVILIANS FROM SOVIET REPATRIATION UNITS ON POLISH TERRITORY IN YEARS 1944-1945World War II drastically changed the previous international balance of power. It also resulted in far-reaching changes in the bilateral relations between the United States of America and the Soviet Union. Their alliance, forced by wartime circumstances, involved collaboration in the diplomatic, military, political and economic scope. One of the areas of the American-Soviet collaboration was also the mutual repatriation of prisoners of war and civilian internees liberated from German captivity. The problem emerged already in 1944 along with the Allied offensive and forced the Allies to take specific measures. It became a priority to develop mechanisms for concentrating the prisoners and internees, keeping their records, protecting them, providing them with appropriate living, medical and sanitary conditions (until they were transferred to the representatives of their states) as well as preparing specific repatriation procedures both in terms of transferring contingents and organizing means of transport and evacuation routes. Months of negotiations led to the agreement signed at the conference in Yalta on 11 February 1945.